Functional imaging of acute kidney injury at 3 Tesla: investigating multiple parameters using DCE-MRI and a two-compartment filtration model = Funktionale Bildgebung des akuten Nierenversagens bei 3 Tesla : Untersuchung verschiedener Parameter unter Nutzung von DCE-MRT und eines 2-Kompartment-Filtrationsmodells - Zöllner, Frank G.; Klotz, Sarah; Höger, Simone; Schad, Lothar R. (Zeitschrift für medizinische Physik, 2015)
To investigate how MR-based parameters reflect functional changes in kidneys with acute kidney injury (AKI) using dynamic contrast enhanced MRI and a two-compartment renal filtration model. MRI data of eight male Lewis rats were analyzed retrospectively. Five animals were subjected to AKI, three native rats served as control. All animals underwent perfusion imaging by dynamic contrast-enhanced MRI. Renal blood volume, glomerular filtration rate (GFR) as well as plasma and tubular mean transit times were estimated from regions-of-interest drawn in the renal cortex. Differences between healthy kidneys and kidneys subjected to AKI were analyzed using a paired t-test. Significant differences between ischemic and healthy kidneys could only be detected for the glomerular filtration rate. For all other calculated parameters, differences were present, however not significant. In rats with AKI, average single kidney GFR was 0.66 ± 0.37ml/min for contralateral and 0.26 ± 0.12ml/ min for diseased kidneys (P = 0.0254). For the healthy control group, the average GFR was 0.39 ± 0.06ml/min and 0.41 ± 0.11ml/min, respectively. Differences between diseased kidneys of AKI rats and ipsilateral kidneys of the healthy control group were significant (P=0.0381). Significant differences of functional parameters reflecting damage of the renal tissue of kidneys with AKI compared to the contralateral, healthy kidneys could only be detected by GFR. GFR might be a useful parameter that allows for a spatially resolved detection of abnormal changes of renal tissue by AKI.
Gesehen am 19.10.2017